MOTIVATION AS A MEANS OF INFLUENCING PROCRASTINATION IN HIGH SCHOOL STUDENTS (Psychology Travelogs, 2024)
The article is devoted to the study of the role of motivation in managing procrastination among high school students. The results of the research work on the influence of various motivational factors on learning efficiency and the ability of students to overcome the tendency to procrastinate are presented. The article discusses the psychological aspects of motivation, such as intrinsic and extrinsic motivation, as well as the influence of self-regulation.The article highlights the results of empirical studies that demonstrate the relationship between different types of motivation and the level of procrastination of students. Motivation, the psychological construct that prompts people to engage in goal-directed behavior, is central to academic success. However, the flip side of this coin is procrastination, a common problem that plagues educational institutions around the world. Procrastination, especially during the high school stages, can have profound consequences for academic performance and overall well-being. Examining the factors that fuel or inhibit motivation and understanding how these dynamics facilitate or moderate procrastination is important for educators, social workers, parents, and psychologists seeking to improve educational outcomes. In particular, the article emphasizes how positive intrinsic motivation can help reduce procrastination and increase academic achievement. It also considers the possibilities of introducing methods of stimulating motivation in the educational process to maintain productivity and self-discipline among high school students. By identifying key motivational drivers and their impact on procrastination behavior, educators can use designed targeted interventions to promote a more supportive learning environment. This article is important for pedagogical practice and helps in understanding the mechanisms of effective motivation management as a tool to combat procrastination in the learning environment.
Keywords: phenomenon of procrastination; motivation; academic goals; high school students; self-regulation; psychological aspects of learning; self-management